Methods for Intracellular Peptidomic Analysis - Eichler, Rosangela A. S.; Martucci, Luiz Felipe; de Castro, Leandro M. [UNESP]; Ferro, Emer S. (Springer Nature, 2024)
Peptides have broad biological significance among different species. Intracellular peptides are considered a particular class of bioactive peptides, whose generation is initiated by proteasomal degradation of cytosolic, nuclear, or mitochondrial proteins. To extract and purify intracellular peptides, which may apply for biological peptides in general, it is important to consider the initial source: tissue, cell, or fluid. First, it is important to proceed fast with inactivation of proteases and/or peptidases commonly present in the biological source of peptides, which might rapidly degrade peptides during the initial process of extraction. The incubation of biological tissues, cells, and fluids at 80 °C for up to 20 min have been sufficient to fully inactivate proteases or peptidases activities. It is particularly important not to acidify the samples at high temperature, because it can lead to nonspecific hydrolysis reactions; particularly, the Asp-Pro peptide bond can be cleaved at acidic environments and elevated temperatures. Unfortunately, not every sample can have proteinases and peptidases denatured by heating the biological source of intracellular peptides. Plasma, for example, when heated at temperatures higher than 55 °C can clot and trap peptides within the fibrin net. Therefore, alternative conditions for inactivating proteinases and peptidases must apply for plasma samples. In this chapter, the most successful methods used in our laboratory to extract intracellular peptides are described.
Keywords: Brain; Formaldehyde; Intracellular peptides; Plasma; Stable isotope